2005
DOI: 10.1080/14636770500037552
|View full text |Cite
|
Sign up to set email alerts
|

Language and values in the human cloning debate: a web-based survey of scientists and christian fundamentalist pastors

Abstract: Over the last seven years, a major debate has arisen over whether human cloning should remain legal in the United States. Given that this may be the 'first real global and simultaneous news story on biotechnology' (Einsiedel et al., 2002, p.313), nations around the world have struggled with the implications of this newly viable scientific technology, which is often also referred to as somatic cell nuclear transfer. Since the successful cloning of Dolly the sheep in 1997, and with increasing media attention pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…A (US-based) survey of research scientists and Christian pastors on views on human cloning similarly revealed strong similarities in what forms of cloning were or were not seen as permissible (Weasel and Jensen 2005). Finally, Tamatea (2008) analysed Christian websites in an attempt to understand lay Christian responses to 'GRIN' (genetics, robotics, information and nano) technologies as they could apply to developments in artificial intelligence.…”
Section: Culture and Religionmentioning
confidence: 96%
“…A (US-based) survey of research scientists and Christian pastors on views on human cloning similarly revealed strong similarities in what forms of cloning were or were not seen as permissible (Weasel and Jensen 2005). Finally, Tamatea (2008) analysed Christian websites in an attempt to understand lay Christian responses to 'GRIN' (genetics, robotics, information and nano) technologies as they could apply to developments in artificial intelligence.…”
Section: Culture and Religionmentioning
confidence: 96%
“…First, the Christian fundamentalist author describes cloning in superficially neutral terms: "scientists create human embryos for medical experimentation." However, both the idea of scientists "creating" human embryos and the idea of "experimentation" are loaded with negative connotations for a Christian fundamentalist audience (Weasel & Jensen, 2005). In the next sentence, "harvesting" cells from "tiny beings," evokes negative images of utilitarian, science-based abortion and "baby farming"…”
Section: Explicit Abortion Codementioning
confidence: 99%
“…However, these values and ideals are not discrete and individuals may identify with the values of both at any one time and incorporate them into the language they use in public discourse (Weasel & Jensen, 2005). As such, participants may draw upon a range of epistemic and ontological resources in formulating their perspectives, even if these conflict with the prevailing norms of a particular institution (Jasanoff, 2004).…”
Section: Contested Moral and Epistemic Authoritymentioning
confidence: 99%